Efficient in vitro Regeneration of a Medicinal Plant Harsinghar (Nyctanthes arbor-tristis L.) - Bansal, S; Bharati, AJ; Bansal, YK (Plant Tissue Culture and Biotechnology, 2013)
In vitro propagation of Nyctanthes arbor-tristis L. has been successfully established from axillary bud explants on MS. Maximum number of multiple shoots was obtained on MS containing BAP (22.2 ?M). Half strength of MS (2% sucrose) supplemented with NAA (10.74 ?M) provided the maximum frequency of root initiation. The plantlets were successfully hardened. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14202 Plant Tissue Cult. & Biotech. 22(2): 137-142, 2012 (December)